Ekstrimisme dalam Tafsir - Asyhari (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
The main cause of radicalism is the distorted understanding of the Qur'an and hadith. One of the Qur'anic verses used to legitimize the precept of the extreme radical group is Q. S al-Maidah: 44. Explicitly this verse seems to justify the radical group's claim that in this world all people have infidels because no one applies the Islamic law perfectly. Sayeed Qutb (d. 1966) is referred to as one of the people of the Muslim Brotherhood in Egypt interpreting the verse on a textual basis. Using the library research method, researchers answered two basic problems; (1) How Sayeed Qutb interprets Q. S al Maidah: 44, (2) How do the scholars interpret Q. S al Maidah: 44?. To answer the researcher to comb the interpretation of Sayeed Qutb in the book of Zilal al-Qur'an, then compare it with the interpretation of the other scholars in the books of interpretation. This research resulted in the conclusion that Sayeed Qutb's interpretation of Q. S al-Maidah: 44 is deviant from the interpretation of all Islamic scholars. The interpretation of Sayeed Qutb precisely corresponds to the interpretation of the Khawarij group at the time of the Caliph Ali ibn Abi Talib. The scholars interpret the passage with three interpretations. First, the meaning of kufr in the verse is a major sin, secondly, that a person is considered infidels when not applying Islamic law because of legal reasons other than Islam is better than Islamic law, third, the passage is revealed to the Jews, that the Jews who did not apply Islamic law were unbelievers.